Workshop on the Emergence of Agentic AI in Financial Technology and Entrepreneurship Development - Lubis, Muharman; Halim, Hendra; Khairi, Fitrah; Syahrizal, Teuku Muhammad; Umuri, Khairil; Fonna, Rizki Putri Nurita; DM, Burhanis Sulthan; Siregar, Fachrul A; Sari, Nurma; Farid, Farid (Jurnal Pengabdian Bakti Akademisi, 2025)
The rapid development of Agentic Artificial Intelligence (AI) and blockchain technology has transformed the global financial and entrepreneurial landscape, posing both opportunities and challenges for young entrepreneurs. This community service activity aimed to enhance the digital literacy and innovation capacity of 100 student entrepreneurs from Universitas Syiah Kuala by introducing practical applications of Agentic AI in financial technology and business development. The activity was conducted in the form of an online workshop, utilizing a service-learning approach, and facilitated by an expert in information systems. The program included knowledge transfer, case studies, and interactive discussions on the implementation of Agentic AI in business decision-making, financial automation, and digital trust. The results showed significant improvement in participants understanding and readiness to adopt such technologies, with marked increases in awareness, interest, and motivation toward innovation. This activity demonstrates an effective model for supporting inclusive entrepreneurship and accelerating the achievement of sustainable development goals through technological empowerment.